ZOON BALANITIS - REVIEW OF 23 CASES - Mendonça Sanches, Maria Lorena (2015)
Introduction: Zoon balanitis or balanitis circumscrita plasmocellularis is a chronic disease of unknown etiology, described mainly in middle-aged or elderly uncircumcised men.Objectives: Characterization of the clinical variables and the response to treatment in patients with histological diagnosis of Zoon balanitis in Hospital de Santa Maria between January 1th 2009 and December 31th 2014.Results: The sample included a total of 23 patients, aged 65 (±11) years old. The clinical differential diagnoses more frequently set were erythroplasia of Queyrat and lichen sclerosus. Concerning therapy most of the patients applied corticosteroids or were submitted to circumcision. From the five patients and the only patient in which CO2 laser therapy was used there is no evidence of recurrence. Of the remaining 17 patients, 4 are under disease progression over corticosteroids topical treatment.Conclusion: Although Zoon balanitis is generally considered a benign condition, the differential diagnoses with squamous cell carcinoma makes the histological confirmation, follow-up and surveillance of this entity mandatory. The persistence of this disease with topical treatments makes chirurgical intervention the gold standard approach in the treatment of these patients.